2017
DOI: 10.1111/resp.12988
|View full text |Cite
|
Sign up to set email alerts
|

Airflow limitation severity and post‐operative pulmonary complications following extra‐pulmonary surgery in COPD patients

Abstract: Background and objective: The association between airflow limitation severity and post-operative pulmonary complications (PPCs) among COPD patients undergoing extra-pulmonary surgery is unknown. We evaluated the association between forced expiratory volume in 1 s (FEV 1 ) and PPC in COPD patients undergoing extra-pulmonary surgery. Methods: Using prospective cohort of PPC evaluation for extra-pulmonary surgery, we identified 694 COPD patients who conducted PPC evaluation before extrapulmonary surgery between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…We initially screened 1106 patients with COPD who underwent preoperative consultations with respiratory physicians and were registered in our institutional, prospectively collected PPC database between March 2014 and January 2015 [14]. We excluded 64 patients with bronchial asthma, determined by Shin SH and Im Y based on the patients' medical history with further confirmation by Park HY.…”
Section: Subjects and Data Sourcesmentioning
confidence: 99%
“…We initially screened 1106 patients with COPD who underwent preoperative consultations with respiratory physicians and were registered in our institutional, prospectively collected PPC database between March 2014 and January 2015 [14]. We excluded 64 patients with bronchial asthma, determined by Shin SH and Im Y based on the patients' medical history with further confirmation by Park HY.…”
Section: Subjects and Data Sourcesmentioning
confidence: 99%
“…16,31 A systematic review of the impact of inhaled corticosteroid treatment on the risk of lung cancer in COPD by Raymakers et al 32 found that randomized studies demonstrated no evidence of benefit, although descriptive studies showed some protection at high doses. Finally, a prospective cohort study by Shin et al 4 reported post-operative respiratory complications in nearly 25% of COPD patients following extra-pulmonary surgery. These complications were related to the severity of airflow obstruction and may have been prevented by perioperative use of bronchodilator therapy.…”
Section: Pharmacological Managementmentioning
confidence: 98%
“…found that randomized studies demonstrated no evidence of benefit, although descriptive studies showed some protection at high doses. Finally, a prospective cohort study by Shin et al . reported post‐operative respiratory complications in nearly 25% of COPD patients following extra‐pulmonary surgery.…”
Section: Copdmentioning
confidence: 99%
See 2 more Smart Citations